Measuring the Technical Efficiency of Turkish Corn Farms by Data Envelopment Analysis and Relations with Farmer's Characteristics - Budak, Fuat; Nagaki, Masakazu; Budak, Dilek B.; Kacira, Ozlem O. (Agricultural Information Research, 2005)
This paper aims to measure the technical efficiency (TE) by identify sources it for corn production in Adana province of Turkey and to explain estimated TE by farmer's characteristics. Data Envelopment Analysis (DEA) was applied to estimate individual score of TE, a relative efficiency index in production. Then, a censored two limit tobit regression model was used to explain the variation in the TE scores by specifying major farmer's characteristics as factors underlying behind. Data were collected by questionnaire from 50 individual farms that use similar inputs, produce the same product and expose to same natural and marketing conditions. Results showed that significant number of farms (68%) operate inefficiently in the survey area. DEA results showed that the quantities of inputs used by farmers were higher than what would be required to maintain the output level. Two limit tobit regression indicated that the variation in TE scores is related to farmer's characteristics such as education level, farm size, farmer's age and family labor. This study suggested that DEA is a promising mean for providing information to productivity improvement. Secondly, managerial capability of farm managers is recognized as an essential method for it.